Political Action: An Eight Nation Study, 1973-1976 - Barnes, Samuel H. ([Verlag nicht ermittelbar], 1984)
The wave of unrest of the late 1960s and early 1970s in advanced industrial societies provided the impetus for this cross-national study of conventional and unconventional forms of political participation. This is an integrated dataset of national sample surveys that were conducted via personal interview during 1973-1976 in eight nations: Great Britain, Germany, Netherlands, Austria, United States, Italy, Switzerland, and Finland. Part 1 contains data gathered in a cross-section sample from 12,588 respondents 16 years of age and over. Part 2 contains data gathered from 1,635 parent-child pairs (with the child being 16-20 years of age) who were part of the first sample and who were further interviewed. The surveys focused on various forms and combinations of political activity ranging from voting to protest actions, and on individual propensities to perform these activities. Among the factors explored in the surveys as contributors to those political activities are personal satisfaction and deprivation, interest in politics, perception of over- and underprivileged groups, left-wing/right-wing self-placement, political attitudes and values, materialist/post-materialist standards, voting behavior, conventional political participation, subjective social class, system responsiveness, political efficacy, attitudes toward young people, ideological sophistication, and satisfaction with government's political, social, and economic policies. Demographic data collected from respondents include age, sex, ethnic origin, number of siblings, father's occupation, family's wealth when young, parents' political preference and education, respondent's religious activity, marital status, number of children, educational level, employment status, organizational membership, current occupation, union membership, and personal, family, and desired income.